2017
DOI: 10.1039/c7cp02527k
|View full text |Cite
|
Sign up to set email alerts
|

Single-photon absorption of isolated collagen mimetic peptides and triple-helix models in the VUV-X energy range

Abstract: (2017). Single-photon absorption of isolated collagen mimetic peptides and triple-helix models in the VUV-X energy range. Physical Chemistry Chemical Physics, 19(28) Cartilage and tendons owe their special mechanical properties to the fibrous collagen structure. These strong fibrils are aggregates of a sub-unit consisting of three collagen proteins wound around each other in a triple helix. Even though collagen is the most abundant protein in the human body, the response of this protein complex to ionizing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 14 publications
(30 citation statements)
references
References 39 publications
8
22
0
Order By: Relevance
“…[6] After electron detachment from R, these charge-dipole interactions do not exist anymore, thus decreasing the complex bindinge nergy, whereas little structurale ffect is expected after electron detachment from the CO 2 À group of vancomycin,b ecause it is not bound to R, and thus can leave the complex without breakingi t, leading to [V+ +RÀ2HÀCO 2 ] À .T he influence of the native structure is also supported by the much lower intensity of the peak attributed to further loss of CO 2 ,l eading to [V+ +RÀ2HÀ2CO 2 ] À :t he loss of both CO 2 groupsm ostlyl eads to dissociation of the complex.W hen photon energy rises from 16 to 24 eV (cf. Figure 6), we observe an increaseo f [VÀHÀCO 2 ] À and [RÀHÀCO 2 ] À .I nt his energy range, we have previously demonstrated that the amount of transferred vibra-tional energy increases, [13,25] it is therefore in line with our hypothesis of [VÀHÀCO 2 ] À and [RÀHÀCO 2 ] À being due to internal conversion and intramolecular vibrationale nergy redistribution after electron detachment.…”
Section: Deprotonated Speciessupporting
confidence: 88%
See 1 more Smart Citation
“…[6] After electron detachment from R, these charge-dipole interactions do not exist anymore, thus decreasing the complex bindinge nergy, whereas little structurale ffect is expected after electron detachment from the CO 2 À group of vancomycin,b ecause it is not bound to R, and thus can leave the complex without breakingi t, leading to [V+ +RÀ2HÀCO 2 ] À .T he influence of the native structure is also supported by the much lower intensity of the peak attributed to further loss of CO 2 ,l eading to [V+ +RÀ2HÀ2CO 2 ] À :t he loss of both CO 2 groupsm ostlyl eads to dissociation of the complex.W hen photon energy rises from 16 to 24 eV (cf. Figure 6), we observe an increaseo f [VÀHÀCO 2 ] À and [RÀHÀCO 2 ] À .I nt his energy range, we have previously demonstrated that the amount of transferred vibra-tional energy increases, [13,25] it is therefore in line with our hypothesis of [VÀHÀCO 2 ] À and [RÀHÀCO 2 ] À being due to internal conversion and intramolecular vibrationale nergy redistribution after electron detachment.…”
Section: Deprotonated Speciessupporting
confidence: 88%
“…Figure ), we observe an increase of [V−H−CO 2 ] − and [R−H−CO 2 ] − . In this energy range, we have previously demonstrated that the amount of transferred vibrational energy increases, it is therefore in line with our hypothesis of [V−H−CO 2 ] − and [R−H−CO 2 ] − being due to internal conversion and intramolecular vibrational energy redistribution after electron detachment.…”
Section: Resultssupporting
confidence: 68%
“…However, a noticeable difference is the presence of peaks assigned to peptide monomers with charge states 2+, 3+, and 4+. They are due to intermolecular dissociation of the triple helix, which is mainly composed of two M 2+ and one M 3+ , as we reported earlier [34]. Therefore, the observation of M 4+ indicates nondissociative ionization of a M 3+ within the triple helix, followed by dissociation into monomers.…”
Section: X-ray Photoabsorptionsupporting
confidence: 75%
“…Figure 3 shows a comparison between mass spectra of the [(PHypG) 10 + 3H] 3+ after irradiation by an x-ray photon beam at 150 eV, and by a C 4+ ion beam at 0.98 MeV/u. The main observation is the striking similarity of the two spectra: For both, the main product cations are [(PHypG) 10 + 3H] 4+ with m/z = 673.5, due to nondissociative ionization (NDI), and backbone fragments, as we recently reported [34]. The latter are mainly singly charged b 3n and y 3n (1 n 4 being a positive integer) fragments coming from glycine-proline peptide bond cleavages, but also b 2 , y 2 , b 4 , y 5 and below m/z = 250, mainly internal fragments formed by at least two backbone cleavages.…”
Section: A Irradiation Of Isolated Collagen Mimetic Peptidessupporting
confidence: 60%
“…7 Furthermore, tunable VUV ionization has been shown to be a selective, yet universal technique in elucidating molecule-specific information since it can distinguish isomers via ionization energy (IE) and absorption cross-sections following rules that are quantifiable. This has allowed its applications in biology, 8,9 combustion chemistry, 10 and atmospheric chemistry. 3 However, liquids have not been often used thus far in single photon ionization mass spectrometry (SPI-MS) applications, because some of them are highly volatile and difficult to retain in vacuum; for a successful VUV SPI-MS measurement, the main chamber vacuum 2 is preferably maintained at 10 -7 Torr.…”
Section: Introductionmentioning
confidence: 99%